Changing scientific meetings for the better - Sarabipour, Sarvenaz (2021)
Scientific conferences are important avenues for researchers to share and discuss research findings, to exchange ideas and insights, and to network for collaboration and career development. Organizing inclusive and useful scientific meetings is a significant responsibility shared by researchers, scientific societies, and other organizations worldwide. Prior to 2020, most conferences were held in-person and provided limited attendance opportunities for many researchers from diverse socioeconomic backgrounds, particularly early career researchers (ECRs), researchers from low- and middle-income countries, and junior principal investigators (PIs)1. Some conferences in select disciplines have implemented valuable changes for the community, becoming more receptive to attendees with families. Due to the COVID-19 pandemic, a major shift has occurred towards virtual conferencing formats, triggering discussions in the scientific community on the current and future formats and organization of conferences. Here we provide recommendations for improving scientific meetings towards more efficient, sustainable, and equitable gatherings.